Genome‐wide analysis of the lignin toolbox of Eucalyptus grandis. Issue 4 (12th February 2015) - Carocha, Victor; Soler, Marçal; Hefer, Charles; Cassan‐Wang, Hua; Fevereiro, Pedro; Myburg, Alexander A.; Paiva, Jorge A. P.; Grima‐Pettenati, Jacqueline
Summary: Lignin, a major component of secondary cell walls, hinders the optimal processing of wood for industrial uses. The recent availability of the Eucalyptus grandis genome sequence allows comprehensive analysis of the genes encoding the 11 protein families specific to the lignin branch of the phenylpropanoid pathway and identification of those mainly involved in xylem developmental lignification. We performed genome‐wide identification of putative members of the lignin gene families, followed by comparative phylogenetic studies focusing on bona fide clades inferred from genes functionally characterized in other species. RNA‐seq and microfluid real‐time quantitative PCR (RT‐qPCR) expression data were used to investigate the developmental and environmental responsive expression patterns of the genes. The phylogenetic analysis revealed that 38 E. grandis genes are located in bona fide lignification clades. Four multigene families (shikimate O ‐hydroxycinnamoyltransferase (HCT), p ‐coumarate 3‐hydroxylase (C3H), caffeate/5‐hydroxyferulate O ‐methyltransferase (COMT) and phenylalanine ammonia‐lyase (PAL)) are expanded by tandem gene duplication compared with other plant species. Seventeen of the 38 genes exhibited strong, preferential expression in highly lignified tissues, probably representing the E. grandis core lignification toolbox. The identification of major genes involved in lignin biosynthesis in E. grandis, the most widely planted hardwood crop world‐wide, provides the foundation for the development of biotechnology approaches to develop tree varieties with enhanced processing qualities. Abstract : Featured paper: see also the Commentary by Strauss & Myburg